Efektivitas Pembelajaran IPS Terintegrasi Dengan Teknologi Informasi Dan Komunikasi Di Era Digital: The Effectiveness of Social Studies Learning Integrated with Information and Communication Technology in the Digital Era - Saepul Bahri, Asep; Hamzah, Erni Irmayanti (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2025)
This study aims to analyze the effectiveness of Information and Communication Technology (ICT) integration in learning Social Studies in the digital era. The background of this research is the urgent need to improve the quality of education through pedagogical innovations that utilize technological advances. In the context of modern education, ICT has great potential to enrich learning experiences, increase student participation, and deepen understanding of social studies materials. The research method used is mixed methods which combines quantitative and qualitative approaches. Quantitative data will be obtained through questionnaires completed by students and teachers, while qualitative data will be collected through in-depth interviews and classroom observations. The samples of this research are social studies students and teachers in several junior high schools (SMP) in Bekasi City that have implemented ICT-based learning. The results of the study are expected to provide an overview of the extent to which ICT integration in social studies learning can improve learning motivation, active involvement of students, as well as learning outcomes. In addition, this study will also identify the supporting and inhibiting factors in the implementation of ICT in social studies classrooms, as well as provide practical recommendations for educators and educational policy makers. The conclusion of this research is expected to contribute significantly to the development of innovative and effective learning methods, as well as supporting efforts to improve the quality of social studies education in the digital era. Thus, this research is expected to be an important reference for curriculum development and learning strategies that are more responsive to technological developments and student needs in the present